Pengaruh Kampanye #PawaiBebasPlastik2021 Terhadap Perilaku Peduli Lingkungan Followers Instagram @iddkp - Hanifah, Wanda; Prananingrum, Elisabeth Nugrahaeni; Sutjipto, Vera Wijayanti (Program Studi Ilmu Komunikasi FISIP UM Buton, 2022)
ABSTRACT Since the Covid-19 pandemic, plastic problems have increased, because they are triggered by changes in behavior and consumption in the community. Environmental care behavior becomes a measuring tool to determine human behavior about the environment. Public awareness of the urgency of the issue of environmental pollution due to plastic waste is also growing, it can be seen from the emergence of various campaigns in Indonesia, thus this study aims to determine the effect of the #PawaiBebasPlastik2021 campaign on the environmental care behavior of Instagram followers iddk. This type of research is quantitative with a survey method. The number of respondents as many as 99. The results of this study indicate that the value of the correlation coefficient test is in the interval 0.61 – 0.80, this value indicates that the #PawaiBebasPlastik2021 campaign has a strong influence on the environmental care behavior of Instagram followers @Iddkp and is positive. Furthermore, based on the value of the results of the determination test, it is known that the coefficient of determination is 43.2% which shows that 43.2% of caring behavior is influenced by the campaign, but the remaining 56.8% is influenced by other factors. Keywords: Social Media, Campaigns, Plastic Waste, Caring Behavior